2014
DOI: 10.4049/jimmunol.1301342
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Initiating Cells from Colorectal Cancer Patients Escape from T Cell–Mediated Immunosurveillance In Vitro through Membrane-Bound IL-4

Abstract: Cancer-initiating cells (CICs) that are responsible for tumor initiation, propagation, and resistance to standard therapies have been isolated from human solid tumors, including colorectal cancer (CRC). The aim of this study was to obtain an immunological profile of CRC-derived CICs and to identify CIC-associated target molecules for T cell immunotherapy. We have isolated cells with CIC properties along with their putative non-CIC autologous counterparts from human primary CRC tissues. These CICs have been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 31 publications
2
84
0
1
Order By: Relevance
“…whether this functional abnormality is caused only by HLA class I APM component downregulation, since it is associated with PD-L1 expression in glioblastoma CICs and with high expression of membrane-bound interleukin-4 in colon CICs. 73,74 Similar results have been reported by Brown and colleagues who used a non-tumor-related cytomegalovirus (CMV) antigen as a model TA. 76 CICs were recognized by cognate T cells only after pulsing with CMV antigen-derived peptide.…”
Section: Ta-specific Mab-based Combinatorial Immunotherapy To Eradicasupporting
confidence: 70%
“…whether this functional abnormality is caused only by HLA class I APM component downregulation, since it is associated with PD-L1 expression in glioblastoma CICs and with high expression of membrane-bound interleukin-4 in colon CICs. 73,74 Similar results have been reported by Brown and colleagues who used a non-tumor-related cytomegalovirus (CMV) antigen as a model TA. 76 CICs were recognized by cognate T cells only after pulsing with CMV antigen-derived peptide.…”
Section: Ta-specific Mab-based Combinatorial Immunotherapy To Eradicasupporting
confidence: 70%
“…Recently Volonté et al reported that CSCs derived from colorectal cancer show weak immunogenicity compared with non‐CSC counterparts. This feature may correlate with the expression of high levels of IL‐4 by the CSCs because neutralization of CSC‐associated IL‐4 can rescue the proliferative activity of T lymphocytes . Based on the results in this study, new immunotherapy protocols to target CSCs might involve blocking inhibitory activity of immunomodulatory molecules as well as activating T cell by CSC specific or associated antigens.…”
Section: Immunological Targeting Of Csc Phenotypesmentioning
confidence: 64%
“…In this study, cell-to-cell contact was required, as co-cultivation without the cellular contact of T lymphocytes with CICs or with CIC-derived cell culture supernatant did not affect their proliferation. Thus, blocking of IL-4 may affect T cell-mediated tumor activity, which could lead to a skewed immune response toward T cell effector responses [62].…”
Section: Il-4 and Il-4 Receptormentioning
confidence: 99%